2008
DOI: 10.1097/mph.0b013e31815c255f
|View full text |Cite
|
Sign up to set email alerts
|

Rhinocerebral Mucormycosis in a Child With Acute Lymphoblastic Leukemia

Abstract: Rhinocerebral mucormycosis in acute lymphoblastic leukemia is manageable with sequential therapy including, amphotericin B, surgery, and risk-adapted chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…Most reports of mucormycosis are of isolated cases, and there are few cases series in the literature. HM is the major underlying disease in these patients …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most reports of mucormycosis are of isolated cases, and there are few cases series in the literature. HM is the major underlying disease in these patients …”
Section: Discussionmentioning
confidence: 99%
“…HM is the major underlying disease in these patients. [12][13][14][15][16][17][18] This study examines the paediatric mucormycosis cases of a larger cases series at a single centre. Of the 158 confirmed cases of mucormycosis, 14% were children.…”
Section: Discussionmentioning
confidence: 99%
“…17 Characteristic histological findings are irregular, broad, non-septate, twisted, ribbon-like, fungal hyphae with the right angle branching. 3,9,18 Fast identification of fungi in frozen sections is available with fluorescent microscopic stain using calcofluor white. 19 Regardless of the tissue or organ involved, pathological hallmarks of mucormycosis include invasion of blood vessels with occlusion causing subsequent tissue reaction of thrombosis, ischemia, and necrosis.…”
Section: Discussionmentioning
confidence: 99%
“… 4 Other single-center pediatric cases have recently been described, including a seven-year-old girl with ALL and rhino-cerebral mucormycosis, two children with acute leukemia and intraoral mucormycosis and four children with ALL and cutaneous mucormycosis; all patients were successfully treated with amphotericin B and surgical debridement. 5-8 Further case reports describe a child with acute leukemia and isolated muscular mucormycosis, one with ALL and fatal gastrointestinal mucormycosis, a nine-year-old boy with ALL and isolated hepatic mucormycosis requiring surgical excision and combined liposomal amphotericin B and posaconazole therapy. Wehl et al reported a boy with ALL relapse experiencing rhino-cerebral-mucormycosis who could not receive surgical debridement because of extensive involvement; his long-term survival of fifteen months was attributed to the long-term administration of liposomal amphotericin B, early neutrophil recovery and slow leukemia progression.…”
Section: Discussionmentioning
confidence: 99%